Methodological development of the determination of the compost mixture ratio - Hunyadi, Gergely (Acta Agraria Debreceniensis, 2010)
The mixing rate of the compost raw materials basically determines the procedure of degradation. In most cases, in practice the real mixing ratio is not equal with the counted ratio – which based on the C/N ratio – and the check of the fulfilled mixing is not possible. The homogeneity of the prism is also one of the fundamentals of the effective degradation process. There is no available method to determine the homogeneity of the compost prism. During our research we examined the reflectance values of different compost mixtures where sewage sludge and rape-straw were used as raw materials. According to our results we built up a regression model which gives the ability to determine the mixing rate (in 5% margin of error) and makes possible to check the homogeneity of the prism together with the access of immediate action.